Dashboard for analyzing SCADA data log: a case study of urban railway in Malaysia - Nazwa Hidayah Mohamad; Hairulazwan Hashim; Nor Aziati Abdul Hamid; Mohd Ismarul Azhar Ismail (Institute of Advanced Engineering and Science, 2021)
The operation of maintenance in the railway industry is a high priority for safety which reflects the train services. The Kelana Jaya Line (KJL) is the leading urban metro train operator among light rail transit (LRT) categories in Malaysia. The main issue in KJL, they are facing huge historical data from the supervisory control and data acquisition (SCADA) logger when organizing the corrective maintenance work schedule. The previous conventional method leads to time constraint which causes redundancy of data reading. Hence, the SCADA dashboard was developed as a tool to structure their work prioritization for weekly planning. It was developed by using Microsoft Power Query and Power Pivot, in the advanced Excel software. The dashboard evaluation was performed based on usability and user experience studies. The evaluation test proves that the dashboard can be used effectively and it’s beneficial to the organizations as well as a contribute towards systematic maintenance.